Yeasts from kefir grains: isolation, identification, and probiotic characterization - Diosma, Gabriela (2013)
Kefir?a traditional beverage whose consumption has been associated with health benefits?is a logical natural product to investigate for new probiotic strains. The aim of the present work was to isolate and identify kefir yeasts and select those with acid and bile tolerance to study their adhesion to epithelial cells and their transit through mouse gut. From 4 milky and 3 sugary kefir grains, 34 yeast strains were isolated and identified by means of classical microbiological and molecular-genetic methods (whole-cell protein pattern, internal-transcribed-spacer amplification, and analysis of restriction-fragment?length polymorphisms). We identified 4 species belonging to 3 genera?Saccharomyces cerevisiae (15 strains), Saccharomyces unisporus (6 strains), Issatchenkia occidentalis (4 strains), and Kluyveromyces marxianus (9 strains)?and selected 13 strains on the basis of resistance to low pH and bile salts. Among the strains selected, Kluyveromyces marxianus CIDCA 8154 and Saccharomyces cerevisiae CIDCA 8112 were further studied. Both strains evidenced the capacity to adhere to epithelial intestine-derived cells in vitro and to survive passage through the gastrointestinal tract of BALB/c mice. The investigation of the potential probiotic features of these kefir-yeast strains should be useful for the development of novel functional foods.